The role of classroom motivation on developing oral proficieny in english language at high school level - Miranda Serano, Manuela del Pilar (UDELAS, 2009)
Then, the purpose of this research is to observe and describe the reasons for this reality from the studends and teachers perspective and obtain some conclusions which can help teachers to improve it.